Glycerin-A New Energy Source for Poultry - Min, Y.N.; Yan, F.; Liu, F.Z.; Coto, C.; Waldroup, P.W. (International Journal of Poultry Science, 2009)
Glycerin, known as glycerol or glycerine, is the principal co-product of biodiesel production, produced through a NaOH- or KOH-catalyzed transesterification of the triacylglycerols in oils or fats with an alcohol. Glycerin is known to be a valuable ingredient for producing food, soaps, cosmetics and pharmaceuticals. Currently, with plenty of glycerin available to the world market, more uses are expected to develop, especially as a potential energy source for poultry diets, with approximately 4,100 kcal/kg of gross energy. Moreover, glycerin also plays a critical role in body cellular metabolism. Results from different laboratories on the use of glycerin as feed energy source for poultry are discussed in this article. Positive responses are obtained with glycerol content up to 10% in poultry diets. The AMEn also has been measured in several experiments. However, more indices such as carcass performance and blood parameters need to be determined in further studies.